The nociceptive response during adult cardiac surgery measured by the qNOX index: A feasibility study - Rogozov, Vladislav; Vaněk, Tomáš; Malý, Marek; Roček, Jan; Kačer, Petr (Biomedical papers of the Medical Faculty of the University Palacky, Olomouc, Czechoslovakia, 2024)
BACKGROUND: Monitoring nociception during general anaesthesia remains a substantial challenge. The Conox monitor uses two EEG indices, the qCon and the qNox. The qNox refers to the probability that a nociceptive stimulation triggers a movement of the patient and the response probability of reaction to nociceptive stimulation. We decided to test the feasibility of monitoring the qNOX index during adult cardiac surgery and to investigate whether this index correlates with hemodynamic and hormonal signs of nociceptive stimulation. METHOD: We enrolled 19 patients undergoing elective cardiac surgery. These were randomised to 2 groups receiving different doses of sufentanil via target controlled infusion: group A (n=9) 0.25 ng/mL and group B (n=10) 0.75 ng/mL. All patients were maintained at the same depth of anaesthesia. We recorded the Conox monitor indices (qNOX, qCON, electromyographic), hemodynamic variables and plasmatic levels of cortisol and noradrenaline. RESULTS: There was significantly higher blood pressure (P=0.013) and plasmatic cortisol (P=0.003) in group A and a significant increase in plasmatic noradrenaline with increasing intensity of surgical stimulation in both groups: A (P=0.001), B (P=0.008). We found no significant corresponding changes in the qNOX index. There was a positive correlation between qNOX and hemodynamic signs of stimulation (P=0.012) and between the qNOX and EMG indices (P=0.013) after endotracheal intubation, but not later after EMG index dropped. CONCLUSION: Our results do not support the assumption that signs of nociceptive stimulation during adult cardiac surgery will be reflected by the qNOX index. This may be related to compounding of qNOX processing and use of muscle relaxants. Further investigation on this field is needed.
Keywords: Hydrocortisone; Anesthesia, General; Cardiac Surgical Procedures; noradrenalin; elektroencefalografie; Norepinephrine; Adult; celková anestezie; Electroencephalography; nocicepce; lidé; dospělí; Nociception; kardiochirurgické výkony; studie proveditelnosti; hydrokortison; Humans; Feasibility Studies